2009
DOI: 10.1590/s0104-66322009000100018
|View full text |Cite
|
Sign up to set email alerts
|

Moisture sorption characteristics of microalgae Spirulina platensis

Abstract: -In recent times, the microalgae Spirulina platensis has been used as a functional ingredient in several food applications; its process involving drying and storage steps. Moisture equilibrium data for adsorption isotherms of microalgae Spirulina were investigated at 10, 20 and 30°C and for desorption, at 40, 50 and 60°C, using the gravimetric static method. The experimental data were analyzed by GAB and BET models. The GAB equation showed the best fitting to the experimental data with R² ≈ 99% and MRE < 10%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
1
2
0
4
Order By: Relevance
“…The results of the desorption isotherms of the olive leaves are presented in Figure 2, where can be verified that the curves showed a sigmoidal behavior and, according to Brunauer et al (1940), these curves could be classified as type II isotherms. Similar results were observed for the olive leaves by Bahloul et al (2008) and microalgae Spirulina platensis by Oliveira et al (2009). Table 2 shows the parameters of the mathematical models (Equations 1 to 3) adjusted to the experimental data, as well as the values of P and R 2 .…”
Section: Resultssupporting
confidence: 70%
“…The results of the desorption isotherms of the olive leaves are presented in Figure 2, where can be verified that the curves showed a sigmoidal behavior and, according to Brunauer et al (1940), these curves could be classified as type II isotherms. Similar results were observed for the olive leaves by Bahloul et al (2008) and microalgae Spirulina platensis by Oliveira et al (2009). Table 2 shows the parameters of the mathematical models (Equations 1 to 3) adjusted to the experimental data, as well as the values of P and R 2 .…”
Section: Resultssupporting
confidence: 70%
“…The value of differential entropy was also estimated and found to mirror the trend for isosteric heat with a decrease from 0.02545 kJ mol −1 K −1 at 1% moisture to 0.0074 kJ mol −1 K −1 at 40% moisture content, indicating that the disorder in the system was strongly moisture dependent. It has been postulated that at lower water activities, the reduced entropies are on account of the restrictive rotation and cross‐interaction of moisture within the monolayer (Oliveira, Rosa, Moraes, & Pinto, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The constant C determines the binding force of water molecules to the primary sites on the product surface (Bhusari et al, 2016), and ranged from 0.3951 (T4) to 117.1637 (CT). Oliveira et al (2009b) found for Spirulina platensis C values ranging from 36.14 to 37.41.…”
Section: Moisture Adsorption Isothermsmentioning
confidence: 92%